EFFECT OF CORN GLUTEN SUPPLEMENT TO LOW QUALITY ROUGHAGES TREATED WITH UREA ON CHEMICAL COMPOSITION AND IV VITRO DIGESTIBILITY - & Mohammed, Hassan (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This study was conducted to determine the effect of corn gluten (0 and 9%) supplementation to low quality roughages (date palm frond, reeds, corn cobs and barley straw) treated with 5% urea on chemical composition and in vitro digestibility,The treatments  were incubated for 0,20 and 30 days at ambient temperature (30-37 C°).The results showed that  nitrogen content, cellulose, metabolizable energy(ME) dry matter InVitro digestibility (IDMD) and Organic matter InVitro digestibility (IOMD)were increased significantly (P